Strategi Koperasi dalam Pemberdayaan UMKM Koperasi Bona Mandiri Jaya - Harahap, Manna; Perkasa, Ripho Delzy (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Micro, Small and Medium Enterprises or abbreviated UMKM are businesses carried out by the community and refer to productive economic businesses owned by individuals or business entities in accordance with the criteria stipulated by Law no. 20 of 2008. Referring to North Sumatra BPS data, the economic census in 2016 revealed that the percentage of non-agricultural MSEs according to business status, 98.84 percent of micro-small businesses and 1.16 percent (Percentage of Non-agricultural MSEs by Business Status, 2016) are medium-sized businesses. big. The method used in this study is a qualitative approach based on descriptive analysis. Based on the analysis of the results of the discussion that in carrying out the empowerment carried out by the Office of Cooperatives and Small and Medium Enterprises with Stephen P. Robbins' Strategy Theory indicators, the process is still quite good.